Konsep pendidikan dalam Islam : suatu kerangka pikir pembinaan filsafat pendidikan Islam - Muhammad Al Naquib Al_Attas (Mizan)
ast c.1,ws.c.2/ast c.3/ast c.4/ir,c.5/tr,c.6/tr,c.7/oen, c.8/oen, c.9/oen, c.10/ast c.11/ast c.12/Oen, c.13/tr,c.14-16/tr,c.17/ tr,c.18/ir,c.19/ast c.20-22